The Influence of Financial Management Quality, Product Innovation, and Ease of Digital Payment on the Performance of Food and Beverage MSMEs in Ponorogo Recency - vinna, sephia (Universitas Dian Nuswantoro Semarang, 2025)
This research aims to analyze the performance of Food and Beverage MSMEs in Ponorogo which is influenced by several variables, namely Financial Management quality, Product Innovation, Digital Payment, and MSME Performance. This research used a quantitative approach method and the Smart PLS 3.29 application. The determination of sample size was based on the formula proposed by Hair et al. (2009): the minimum sample size is 5-10 times the number of indicators. With 17 indicators and 7 sample sizes, a minimum of 119 samples were obtained. This research uses a non-probability sampling method with a purposive sampling technique. The results of this study found that the quality of financial management has a significant positive effect on MSME performance, supporting operational efficiency and financial stability. In contrast, product innovation does not show a significant impact, possibly due to a lack of relevance to the market or a weak marketing strategy. Digital payments have a significant positive impact, increasing transaction efficiency and customer experience, thereby encouraging MSME business growth. This research focuses on food and beverage MSMEs spread across Ponorogo Regency. This research analyzes the influence of financial management quality, product innovation, and digital payments on MSME performance. By combining these three factors, this research provides a more complete understanding of what influences the success of MSMEs. The results also provide practical input to help MSMEs develop, especially by utilizing technology and good financial management